2012
DOI: 10.1016/j.jcrs.2012.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of corneal astigmatism in cataract surgery candidates at a teaching hospital in Shanghai, China

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
69
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 16 publications
10
69
7
Order By: Relevance
“…1 In a previous study, 2 44% to 54% of patients with cataract had corneal astigmatism higher than 1.0 diopter (D) based on the type of keratometer. Several other studies [3][4][5] reported similar results. Corneal astigmatism can be corrected during cataract surgery using various methods, including implantation of a toric IOL.…”
supporting
confidence: 71%
“…1 In a previous study, 2 44% to 54% of patients with cataract had corneal astigmatism higher than 1.0 diopter (D) based on the type of keratometer. Several other studies [3][4][5] reported similar results. Corneal astigmatism can be corrected during cataract surgery using various methods, including implantation of a toric IOL.…”
supporting
confidence: 71%
“…The reasons for this were the changes in the eyelid along with aging and also the pressures of these changes on the cornea leading to astigmatic changes on the cornea [17]. Guan et al [6] investigated 827 Chinese patients, and less than 1 D astigmatism was found in 54.5% of patients and against-the-rule increased and linear regression with age. Chen et al [8], and Khan and Muhtaseb [9] were found similar result.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve best postoperative visual outcomes, spherical and astigmatic components of refractive error should be corrected during cataract surgery. 1 The prevalence of corneal astigmatism has been widely reported in several parts of the world.…”
Section: Introductionmentioning
confidence: 99%